Research on the impact of marine economic development in coastal areas on regional economic resilience: evidence from China - Wang, Hao; Yang, Jicong; Wu, Hongsen; Niu, Congcong (Frontiers in Marine Science, 2024)
Marine economy is a valuable pillar for the development of coastal areas. It is of profound significance to explore the influence of marine economy development on economic resilience of coastal areas. This paper constructs an economic resilience assessment framework based on resistance, adaptability, and evolutionary power, adopts the entropy method to calculate the economic resilience development level in China's coastal areas from 2006 to 2019, and examines in detail the driving factors affecting the economic resilience from the indicator level. Furthermore, panel regression models are used to explore the influence of marine economic development on the economic resilience of China's coastal areas and its mechanism of action. The results show that: (1) China's coastal areas have an overall trend of rising economic resilience. The spatiotemporal differentiation characteristics of different economic resilience factors are significant.(2) Factors such as regional economic scale, innovation input, industrial transformation, resident income, consumption scale, degree of marketization, and financial scale are key factors to enhance the economic system resilience of coastal areas. (3) There is a significant positive impact of the marine economy on the economic resilience of coastal areas, and this promotion effect is regulated and constrained by the level of diversification of marine industries and the level of concentration of marine industries. (4) Heterogeneity analysis shows that there are significant individual differences in the impact of Marine economy on economic resilience, and its marginal effect first increases and then decreases. The corresponding policy implications are further analyzed based on the research results.